Fibre lasers for optical communication systems - Lai, Yicheng (2008)
The transmission capacity of long haul lightwave system experienced 100 times increase over the past 6 years. Both in system and component levels, rapid evolutions have been taking place to meet the future demand of services and number of users. Fibre Bragg gratings have fast become an enabling technology that provides reliable solutions to a multitude of design problems in fibre systems. Among all, grating-based fibre lasers demonstrate numerous characteristics suitable for optical communication systems and show great potentials to be the transmitter sources for next generation technology like Wavelength Division Multiplexing (WDM) systems.